2000
DOI: 10.1159/000012155
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Serum Interleukin-6 Levels to Predict Benefits of Medroxyprogesterone Acetate in Advanced or Recurrent Breast Cancer

Abstract: Treatment of advanced or recurrent breast cancer with medroxyprogesterone acetate (MPA) shows high response rates and the accessory effects of appetite stimulation, improvement in performance status (PS) and bone marrow protection. In recent years, interleukin-6 (IL-6) has been reported to cause cachexia. In this study, to clarify the significance of IL-6 in advanced or recurrent breast cancer, the relationship between the IL-6 level and clinical findings or effect of MPA was investigated. Sixty-five patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…5,6,10,[12][13][14][15][16] In agreement with the available literature, the current analysis found shorter survivals in those patients with high IL-6 levels (Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5,6,10,[12][13][14][15][16] In agreement with the available literature, the current analysis found shorter survivals in those patients with high IL-6 levels (Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4] Accumulating data suggest that the plasma levels of some cytokines might reflect the activity of the immune system against the tumor and correlate to the extent of disease and prognosis. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Interleukin (IL)-6, for example, can stimulate cell growth and angiogenesis, and induce resistance to therapy in cancer cells 1,3,20 and high serum IL-6 levels have been found to predict a poor clinical outcome. 5-8,10 -16 In addition, animal studies have shown an impairment in the host response against the tumor due to an abnormal production of IL-10 by the malignant and host immune cells.…”
mentioning
confidence: 99%
“…Nevertheless, these results support the studies of Yokoe et al [44]. Another study, done by Nishimura et al [46], analyzed the significance of IL-6 in advanced or recurrent breast cancer, the relationship between the IL-6 level and clinical findings or effect of medroxyprogeterone acetate (MPA, presumed to inhibit IL-6 production). They found serum IL-6 to be significantly higher in recurrent cases (6.5 ± 7.48 pg/ml), especially in those with visceral metastasis, than in non-recurrent cases (1.96 ± 1.38 pg/ml).…”
Section: Il-6 Serum Levels and Breast Cancer Patientssupporting
confidence: 77%
“…Our results are in accordance with study done by Kozlowski et.al, which assessed the concentration of IL-6 in blood serum of breast cancer patients to determine whether it correlates with the disease progression [8]. Another study by Nishimura et al [11] analyzed the significance of IL-6 in advanced or recurrent breast cancer, with serum IL-6 to be significantly higher in recurrent cases (6.5 ± 7.8 pg/ml), especially in those with visceral metastasis, than in non-recurrent cases (1.96 ± 1.38 pg/ml). Jablonska et al [12] found serum levels of IL-6 in breast cancer patients in stage II to be higher (16.7 ± 8.7) than in the control (9.81 ± 3.96 pg/ ml), furthermore, breast cancer patients in stage III/IV had increase serum levels of IL-6 (29.4 ± 12.9) compared with stage II, and they concluded that changes in values of certain cytokines could have a diagnostic and prognostic role in cancer disease.…”
Section: Discussionsupporting
confidence: 93%